ANALYSIS OF CLUSTER BASED ROUTING IN WIRELESS SENSOR NETWORKS (International Journal of Engineering and Computer Science, 2017)
The limited resources of the sensor nodes, designing energy-efficient routing mechanism to prolong the overall network lifetime between one of the most important technologies in wireless sensor networks(WSN). As an active branch of routing technology, cluster-based routing protocols have proven to be effective in network topology management, energy minimization, data aggregation and so on. This paper present a survey of state-of-the art routing techniques in WSNs. First outline the clustering architecture in WSNs, and classify the proposed approaches based on their objectives and design principles. Furthermore highlight the challenges in clustering WSNs, including rotating the role of cluster heads, optimization of cluster size and communication mode, followed by a comprehensive survey of routing techniques. Finally the paper concludes with possible future research areas.